Conductivity and dielectric properties of proton conducting poly (Vinyl)chloride (PVC) based gel polymer electrolytes - Siti Khatijah Deraman,; Mohamed, N.S.; Subban, R.H.Y (Universiti Kebangsaan Malaysia, 2013)
Poly (vinyl) chloride (PVC)-NH4I-EC films have been prepared by the solution cast technique. The sample containing 30 wt.% NH4I exhibited the highest room temperature conductivity of 4.60 × 10-7 S cm-1. The conductivity increased to 1.08 × 10-6 Scm-1 when 15 wt.% of ethylene carbonate (EC) was added to 70 wt.% PVC - 30 wt.% NH4I. The effects of ethylene carbonate (EC) addition on the frequency dependent dielectric properties of PVC based electrolytes were investigated by electrochemical impedance spectroscopy (EIS), in the temperature range of 300 K to 373 K. The dielectric properties and ac conductivity of the samples prepared have been analyzed. The values of dielectric constant were found to increase with increasing conductivity of the samples. Analysis of the ac conductivity data revealed the electrolytes to be of the non-Debye type with conduction mechanism of the overlapping-large-polaron-tunneling (OLPT) model.